Association between blood pressure and intracranial artery stenosis in a Chinese population - Song, Xiaowei (J Clin Hypertens (Greenwich), 2019)
The association between blood pressure and intracranial artery stenosis (ICAS) in different age groups has not been elucidated. Using data from the “China Hypertension Survey,” we conducted a cross‐sectional analysis of the association between blood pressure parameters and ICAS. In this study, participants older than 35 years were selected by stratified, multistage random sampling. Blood pressure was measured repeatedly at rest, and ICAS was assessed by transcranial doppler ultrasound. Binary logistic regression analysis was used to demonstrate the association between different blood pressure indicators and ICAS. Of the 3640 participants included (mean age 63 ± 13 years old, 57.8% female), systolic blood pressure (SBP) and pulse pressure (PP) were associated with ICAS in the general population; the multivariable adjusted odds ratio (OR) and corresponding 95% confidence interval (95% CI) of ICAS and multivessel stenosis were 1.32 (1.21, 1.45) and 1.29 (1.14, 1.46) per standard deviation (SD) increase in SBP and 1.44 (1.30, 1.59) and 1.52 (1.33, 1.74) for PP, respectively. Further analysis of this association in different age groups revealed inconsistent results between SBP and ICAS. Prehypertension (120 ≤ SBP < 140) could predict ICAS in the older group but not in the younger group, and the positive association between SBP and multivessel stenosis disappeared in the younger age group (P > .05 in all SBP subgroups). In conclusion, SBP and PP could not only identify ICAS in the middle‐aged and elderly population but could also provide some information about ICAS burden; however, these associations need to be interpreted differentially based on age subgroup.